MACROINVERTEBRATE BIOMASS AND NUTRIENT CHARACTERISTICS OF SEDIMENT OF A PERTURBED URBAN LAGOON IN NIGERIA. - UWADIAE, R.E. (Nigerian Journal of Fisheries, 2018)
The macroinvertebrate biomass and nutrient characteristics of a perturbed urban lagoon in Southwest Nigeria were investigated by a monthly sample collection and analysis for six months. A generally low macroinvertebrate biomass was observed in this study. Of the total 7,782.3 gm-2 recorded, mollusca contributed 7,715 gm-2 and accounted for 99.1 % of the total macroinvertebrate biomass. The gastropod Pachymelania aurita was the most abundant taxa, the species recorded a biomass of 2700.25 gm2 and accounted for 35 % of molluscan biomass. This was followed by Tympanotonus fuscatus another gastropod which accounted for 22 % (biomass 1697.3 gm-2 ) of molluscan biomass. Annelida recorded a biomass of 67.3l gm2 from the single genus Nereis collected from the study area and accounted for 0.9% of the total benthic macroinvertebrate biomass. There was high variability in values of sediment protein and lipid among study stations during sampling months. Whereas protein fluctuated between 0.13 and 1.74%, lipid varied from 0.01 to 0.21%. Relatively higher values of protein were recorded in this study. The poor nutrient content of sediment and low macroinvertebrate biomass observed in this study are likely the resultant effects of sediment disturbance arising from sand mining activities in the study area.